Skull of Capybara (Hydrochoerus hydrochaeris) - Morphometric Parameters - Ferrari, Lorena Cardozo [UNESP]; Macedo Pereira, Fernanda Mara Aragão [UNESP]; Farha, Aline Herrera [UNESP]; Oliveira, Elton Luís Ritir [UNESP]; Schimming, Bruno Cesar [UNESP] (Universidade Federal do Rio Grande do Sul, 2022)
Background: The capybara (Hydrochoerus hydrochaeris) is the largest rodent in the world. They are territorial animals, and live in social groups, commonly occurring in anthropized area, what has attracted the attention of researchers in relation to this animal species, since it is the host of the Amblyomma cajennese tick that transmits spotted-fever to humans and are responsible for severe impact on livestock and public health. The skull is a part of the axial skeleton that enclosing the brain, sensory organs and digestive and respiratory structures. Moreover, the phenotypic appearance of the capybara head depends on the shape of the skull. Thus, the aim of this study was to describe the reference values of cranial measurements of capybaras. The knowledge of morphometric parameters of skull is pivotal for veterinary treatment of pathological conditions and taxonomic affiliation. Materials, Methods & Results: Eight capybaras (Hydrochoerus hydrochaeris) skulls were used in this study, irrespective of age and sex. The skulls belonging to the anatomical collection of the Laboratory of Wildlife Anatomy and Anatomical Museum, Department of Anatomy, Universidade Estadual Paulista Júlio de Mesquita Filho, UNESP, Botucatu, São Paulo. A total of 35 morphometric parameters were performed using a digital caliper and 6 cranial indices were calculated. All investigated features were expressed as mean ± standard deviation. Anatomically, capybara skull were elongated, rectangle-like and consisted of cranial and facial bones. The morphometric parameters were used to calculate the following craniometrics indices: skull index (57.86 ± 3.62), cranial index (50.49 ± 2.08), facial index (49.22 ± 3.82), basal index (33.98 ± 0.86), nasal index (26.73 ± 3.1), and the foramen magnum index (149.61 ± 1.07). Moreover, the facial part length (mean 137.90 mm) and cranium part length (mean 87.76 mm) also were calculated. The facial part length was a distance from the cribriform plate of the ethmoid bone to the rostral edge of the incisive bone and, the cranium part length was a distance from the external occipital protuberance to the cribriform plate of the ethmoid bone. Discussion: This study established morphometric parameters in the capybara skull. The craniometric measurements showed in this study are compatible with reported in other studies in the capybara skull, although the most parameters measured in this study were not calculated in previous studies of the capybara skull. Moreover, none of the cranial indices calculated in this study were previously calculated. Based on some cranial measurements, the 8 capybaras used in this study could be classified into subadult (4) and adults (4). The foramen magnum showed a dorsal triangular notch in the capybara skull differently from described in the Cavia spp., and similar to reported to other rodent as Gambian rat and other mammals species such as maned wolf, four-toed hedgehog, and dromedaries. The rectangular shape of the capybara skull is different from that found in other caviids rodents such as Brazilian guinea pig. The capybara skull showed greater development of the facial part in relation to the cranial part, which allows to relate the skull shape with the skull shape presented by dolichocephalics dogs. This feature is commonly reported in large caviomorph rodents. Probably, this morphology is compatible with the ecology and phylogeny of the species.
Keywords: capybaras; craniometry; cranium; veterinary anatomy; wildlife